C–C bridged Ni(II) complexes bearing β‐keto‐9‐fluorenyliminato ligands prepared by different in situ bonding mechanisms and their use in catalytic (co)polymerization of norbornene and styrene. (21st December 2018) - He, Xiaohui; Wang, Suli; Yang, Yingping; Tu, Guangshui; Zhang, Feng; Huang, Shengmei; Duan, Yapeng; Zhu, Chuanyi; Cheng, Changwen; Chen, Defu
Abstract : Two C–C bridged Ni(II) complexes bearing β‐keto‐9‐fluorenyliminato ligands with electron‐withdrawing groups (─CF3 ), NiPhC(O)CHC[N(9‐fluorenyl)]CF2 2 (Ni1 ) and NiCF3 C(O)CHC[N(9‐fluorenyl)]Ph2 (Ni2 ), were synthesized by metal coordination reaction and different in situ bonding mechanisms. The C–C bridged bonds of Ni1 were formed by in situ intramolecular trifluoromethyl and 9‐fluorenyl carbon–carbon cross‐coupling reaction and those of Ni2 were formed by in situ intramolecular 9‐fluorenyl carbon–carbon radical coupling reaction mechanism. The obtained complexes were characterized using 1 H NMR spectroscopy and elemental analyses. The crystal and molecular structures of Ni1 and Ni2 with C–C bridged configuration were determined using X‐ray diffraction. Ni1 and Ni2 were used as catalysts for norbornene (NB) polymerization after activation with B(C6 F5 )3 and the catalytic activities reached 10 6 gpolymer molNi −1 h −1 . The copolymerization of NB and styrene catalyzed by the Ni1 /B(C6 F5 )3 system showed high activity (10 5 gpolymer molNi −1 h −1 ) and the catalytic activities decreased with increasing feed content of styrene. All vinyl‐type copolymers exhibited high molecular weight (10 4 g mol −1 ), narrow molecular weight distribution ( M w / M n = 1.71–2.80), high styrene insertion ratios (11.13–50.81%) and high thermal stability ( T d > 380°C) and could be made into thin films with high transparency in the visible region (400–800 nm). Abstract : Novel C–C bridged Ni(II) complexes bearing β‐keto‐9‐fluorenyliminato ligands with electron‐withdrawing groups were synthesized by metal coordination and different in situ intramolecular bonding mechanisms, and applied in the (co)polymerization of norbornene and styrene. The copolymers were obtained with high styrene monomer content, and exhibited high thermal stability, narrow molecular weight distribution and high transparency in the visible region.